Pengaruh Ping of Death pada Perangkat dengan Sistem Keamanan Jaringan NIDS dan HIPS - Faisal Hakim Indrayana; Erwien Christianto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The security system on the network was created virtually via OpenvSwitch using the NIDS and HIDS methods designed using SNORT. The results of the Ping of Death attack cause the CPU performance to be very high, so that the computer works optimally due to the large number of packets going to the Server computer.